Automation of signal processing of electric field intensity sensors included in information-measuring system - S. S. Kolmogorova; D. S. Baranov; A. S. Kolmogorov; S. V. Biryukov (Омский научный вестник)
The adverse effect of electromagnetic fields on a person makes it necessary to exclude his presence in the measurement process. Therefore, the tasks associated with the automation of measurement parameters of electromagnetic fields are relevant. In this regard, the article deals with the automation of the processing of measuring signals from sensitive elements of sensors in the measurement process. Sensors of electric field, having from one to six sensitive electrodes (depending on the modification) are involved in the examination. Signal processing and algorithmic operations are carried out on the Siemens S7-300 platform with Siwerex weighing modules. A distinctive feature is the algorithm for processing the readings of sensors in the process of obtaining data. Integration of the lower level into a third-party SCADA system is possible. The results of the study made it possible to conclude that with direct measurements it is necessary to take into account the overlap area of the sensor sensitive electrodes and the rate of change of its readings; the implementation of correction algorithms for the specified parameters allows the system to quickly adapt to changes in process conditions and achieve high measurement accuracy; Siemens WinCC Flexeble software should be used as a man-machine interface.